Language Use and Sustainable Development: Opportunities and Challenges for Policy-Makers and Educators in Northeast Vietnamese Areas - Ha Ngan Ngo; Maya Khemlani David (Universitas Jambi, Magister Program of English Education Department, 2018)
Vietnam represents a country with 54 ethnic groups; however, the majority (88%) of the population are of Vietnamese heritage. Some of the other ethnic groups such as Tay, Thai, Muong, Hoa, Khmer, and Nung have a population of around 1 million each, while the Brau, Roman, and Odu consist only of a hundred people each. Living in northern Vietnam, close to the Chinese border (see Figure 1), the Tay people speak a language of the Central Tai language group called Though, T'o, Tai Tho, Ngan, Phen, Thu Lao, or Pa Di. Tay remains one of 10 ethnic languages used by 1 million speakers (Buoi, 2003). The Tày ethnic group has a rich culture of wedding songs, poems, dance, and music and celebrate various festivals. Wet rice cultivation, canal digging and grain threshing on wooden racks are part of the Tày traditions. Their villages situated near the foothills often bear the names of nearby mountains, rivers, or fields. This study discusses the status and role of the Tày language in Northeast Vietnam. It discusses factors, which have affected the habitual use of the Tay language, the connection between language shift and development and provides a model for the sustainability and promotion of minority languages. It remains fundamentally imperative to strengthen and to foster positive attitudes of the community towards the Tày language. Tày’s young people must be enlightened to the reality their Tày non-usage could render their mother tongue defunct, which means their history stands to be lost.